Evaluation of microshear bond strength and nanoleakage of etch-and-rinse and self-etch adhesives to dentin pretreated with silver diamine fluoride/potassium iodide: An in vitro study - Karthik Selvaraj; Vidhya Sampath; V Sujatha; S Mahalaxmi (Wolters Kluwer Medknow Publications, 2016)
Aims: The aim of this in vitro study was to comparatively evaluate the microshear bond strength (MSBS) of etch-and-rinse and self-etch (ER and SE) bonding systems to dentin pretreated with silver diamine fluoride/potassium iodide (SDF/KI) and nanoleakage at the resin-dentin interface using transmission electron microscope (TEM). Subjects and Methods: Seventy-two dentin slabs of 3 mm thickness were prepared from extracted human permanent third molars and divided into four groups (n = 18) based on the dentin surface treatment as follows: (1) ER adhesive bonding without dentin pretreatment; (2) SDF/KI pretreatment of dentin followed by ER adhesive bonding; (3) SE adhesive bonding without dentin pretreatment; and (4) SDF/KI pretreatment of dentin followed by SE adhesive bonding. Resin composite was built on the dentin slabs to a height of 4 mm incrementally, and dentin-composite beams of approximately 1 mm 2 cross-sectional area were prepared. The beams were subjected to MSBS analysis, and the fractured surface was observed under scanning electron microscope to determine the mode of failure. The resin-dentin interface was examined under TEM for evaluation of nanoleakage. Statistical Analysis Used: One-way ANOVA followed by Tukey's post hoc multiple comparison tests. Results: Pretreatment of dentin with SDF/KI increased the MSBS of ER and SE adhesives, though not statistically significant, except between Groups 2 and 3. In all the groups, the predominant mode of failure was adhesive followed by cohesive in resin, mixed and cohesive in dentin. TEM examination of resin-dentin interface showed that pretreatment with 38% SDF/KI reduced nanoleakage regardless of the type of bonding system used. Conclusions: Pretreatment of dentin with SDF/KI minimized nanoleakage at the resin-dentin interface without adversely affecting the bond strength of resin composite to dentin.